(untitled) (GUB Journal of Science and Engineering, 2024)
Basic knowledge of chemical events in the gaseous or liquid phase, as well as on surfaces, is required to determine the macroscopic process. The structure of ionic liquids were investigated using quantum chemistry. Cation and anion can bond together, according to the findings. Their binding and interaction energies reveal that they are produced by hydrogen bonds. The mechanism of a room temperature ionic liquid, such as [BMIM][Cl] (1-butyl-3-Methylimidazolium chloride) monomer, was studied using Density functional theory (DFT) computations using the modern continum solvation model (IEFPCM-SMD). Ionic liquid [IL] contains both anions and cations, allowing for greater intermolecular interactions. By analyzing the relative minimum energy of [BMIM][Cl] in the presence and absence of water, we were able to establish the minimum energy structures and probable Cl anion binding sites in [BMIM][Cl] ionic liquid. We have found that all 1-butyl-3-methylimidazolium halide ILs investigated had trans conformations due to the butyl group’s dihedral angles. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 9(1), 2022 P 66-70